PURDUE ONLINE WRITING LAB IS AN EFFECTIVE TOOL TO ENHANCE WRITING SKILLS - Akmalova , Zulfiya (Educational Research in Universal Sciences, 2024)
Students have always found writing to be challenging because it is not straightforward. It requires much effort, planning, preparation and other skills to produce a piece of writing. At tertiary education, learners are normally assigned to write essays, articles, and lengthy papers. Thus, for students it is imperative to learn how to compose a well-organized and quality paper. The author of this article recommends to use Purdue Online Writing Lab. As it offers up-to-date resources on anything about writing.